Is it okay to use the nicotine patch during pregnancy?. Issue 2 (February 2015) - Brandenburg, Dana; Pereira, Chrystian; Adam, Patricia
Abstract : Evidence‐Based Answer : Evidence is conflicting on the efficacy and safety of nicotine replacement therapy (NRT) in pregnancy. Guidelines recommend against NRT until more evidence is available (SOR: C, expert opinion).